The efficacy of blind versus real-time ultrasound-guided percutaneous renal biopsy in developing country. (May 2019) - Pongsittisak, Wanjak; Wutilertcharoenwong, Naphat; Ngamvichchukorn, Tanun; Kurathong, Sathit; Chavanisakun, Chutima; Teepprasan, Tavichai; Prommool, Surazee; Srisawat, Nattachai
Introduction: Renal biopsy is a useful diagnostic procedure. In developing countries, two techniques of renal biopsy, blind percutaneous renal biopsy and real-time ultrasound-guided percutaneous renal biopsy, have been performed. The majority of studies compared these using different types and sizes of biopsy needle. The aim of this study was to compare both techniques in resource constraint country. Method: We reviewed renal biopsy database, between 1 January 2014 to 30 June 2017. The primary outcome was the total number of glomeruli. The other outcomes were tissue adequacy and bleeding complications. We also analyzed multivariable logistic regression to find factors associated with tissue adequacy and bleeding complications. Result: Of the 204 renal biopsies, 100 were blind percutaneous renal biopsy and 104 real-time ultrasound-guided percutaneous renal biopsy. The number of native renal biopsies was 169 (82.8%). Baseline characteristics of two groups were comparable. The mean number of total glomeruli from real-time ultrasound-guided percutaneous renal biopsy was significantly more than blind percutaneous renal biopsy (20.8 ± 12.1 vs 16.0 ± 13.0, p = 0.001). The real-time ultrasound-guided percutaneous renal biopsy obtained more adequate tissues than blind percutaneous renal biopsy (45.2% vs 16%, p < 0.001) and was the only factor associated with adequate tissue. Moreover, 16 renal biopsies from blind percutaneous renal biopsy obtained inadequate tissue. The overall bleeding complications were not statistically different. We found being female, lower eGFR and lower hematocrit were associated with bleeding complications. Conclusion: In comparison with blind percutaneous renal biopsy, real-time ultrasound-guided percutaneous renal biopsy obtained more adequate tissue and number of glomeruli. While the complications of both were comparable. We encourage to practice and perform real-time ultrasound-guided percutaneous renal biopsy in resource constraint countries.